Licensed moneylending industry as an alternative financial service in Malaysia - Sandhu, Daljit Kaur; Muhammad Arif, Afida Mastura; Abu Bakar, Elistina; Abdul Rahim @ Abdul Wahab, Husniyah (Malaysian Financial Planning Council, 2019)
Moneylending in Malaysia began informally before independence with the Nattukottai Chettiars pillared by their temple institution, and the Punjabi Sikh community supported by their motherland Punjab (Lal, 2003; Manjit, 1991). It was spearheaded by mutual trust between lenders and borrowers using hand written or verbal IOUs. Borrowers were primarily adult males seeking funds to conduct businesses, resulting in prompt repayments. It is unfortunate that due to the Japanese occupation of Malaya in 1942 to 1945, and the implementation of the requirement of having Malaysian citizenship to practise licensed moneylending with the passing of Moneylenders Act 1951.